Computational analysis of deposition and translocation of inhaled nicotine and acrolein in the human body with e-cigarette puffing topographies. Issue 5 (4th May 2018) - Haghnegahdar, Ahmadreza; Feng, Yu; Chen, Xiaole; Lin, Jiang
ABSTRACT: Recently, toxicants such as formaldehyde and acrolein were detected in electronic cigarette (EC) aerosols. It is imperative to conduct research and provide sufficient quantitative evidence to address the associated potential health risks. However, it is still a lack of informative data, i.e., high-resolution local dosimetry of inhaled aerosols in lung airways and other systemic regions, due to the limited imaging resolutions, restricted operational flexibilities, and invasive nature of experimental and clinical studies. In this study, an experimentally validated multiscale numerical model, i.e., Computational Fluid-Particle Dynamics (CFPD) model combined with a Physiologically Based Toxicokinetic (PBTK) model is developed to predict the systemic translocation of nicotine and acrolein in the human body after the deposition in the respiratory system. In-silico parametric analysis is performed for puff topography influence on the deposition and translocation of nicotine and acrolein in human respiratory systems and the systemic region. Results indicate that the puff volume and holding time can contribute to the variations of the nicotine and acrolein plasma concentration due to enhanced aerosol deposition in the lung. The change in the holding time has resulted in significant difference in the chemical translocation which was neglected in a large group of experimental studies. The capability of simulating multiple puffs of the new CFPD-PBTK model paves the way to a valuable computational simulation tool for assessing the chronic health effects of inhaled EC toxicants. Copyright © 2018 American Association for Aerosol Research